Analisis Kritis Teori Belajar Sosiokultural Terhadap Karakter Sosial Komunikatif Siswa di Era Digitalisasi.rtf - Kurniawan, M. Riski; Mustakim, Iqbal; Harto, Kasinyo; Suryana, Ermis (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This paper has the main objective of the process of developing sociocultural learning theory as an effort to understand and inculcate social communicative character values in the current digitalization era. This is a form of business that can lead students to social awareness and also the process of understanding the role that exists for how to live a proper life in the surrounding environment. This research uses a qualitative approach with the type of library research method. While the approach used is descriptive analysis which emphasizes in-depth analysis of existing data sources. The conclusion obtained is that with sociocultural learning theory with PAI learning there is continuity in a position that makes the environment an important part of instilling communicative social character values. As a social human being, students must have the values of communicative social character in themselves as a form of balance that occurs in living this life.